Obligatory parthenogenesis and TE load: Bacillus stick insects and the R2 non‐LTR retrotransposon. (5th May 2016) - Bonandin, Livia; Scavariello, Claudia; Mingazzini, Valentina; Luchetti, Andrea; Mantovani, Barbara
Abstract: Transposable elements (TEs) are selfish genetic elements whose self‐replication is contrasted by the host genome. In this context, host reproductive strategies are predicted to impact on both TEs load and activity. The presence and insertion distribution of the non‐LTR retrotransposon R2 was here studied in populations of the strictly bisexual Bacillus grandii maretimi and of the obligatory parthenogenetic Bacillus atticus atticus . Furthermore, data were also obtained from the offspring of selected B. a. atticus females. At the population level, the gonochoric B. g. maretimi showed a significantly higher R2 load than the obligatory parthenogenetic B. a. atticus . The comparison with bisexual and unisexual Bacillus rossius populations showed that their values were higher than those recorded for B. a. atticus and similar, or even higher, than those of B. g. maretimi . Consistently, an R2 load reduction is scored in B. a. atticus offspring even if with a great variance. On the whole, data here produced indicate that in the obligatory unisexual B. a. atticus R2 is active and that mechanisms of molecular turnover are effective. Furthermore, progeny analyses show that, at variance of the facultative parthenogenetic B. rossius, the R2 activity is held at a lower rate. Modeling parental‐offspring inheritance, suggests that in B. a. atticus recombination plays a major role in eliminating insertions rather than selection, as previously suggested for unisexual B. rossius progeny, even if in both cases a high variance is observed. In addition to this, mechanisms of R2 silencing or chances of clonal selection cannot be ruled out.